2004
DOI: 10.1159/000080050
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Viral Vector for Targeting Gene Therapy to Motoneurons in the CNS

Abstract: Gene therapy vectors that can be targeted to motoneuronal cells are required in the field of neurodegenerative diseases. We propose the use of the atoxic fragment C of tetanus toxin (TTC) as biological activity carrier to the motoneurons. Naked DNA encoding β-galactosidase-TTC hybrid protein was used to transfect muscle cells in vivo, resulting in a selective gene transfer of the enzymatic activity to the CNS. In the muscle, level expression of β-galactosidase was readily detectable 24 h after injection, reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 70 publications
0
7
0
4
Order By: Relevance
“…One of the most well-known hybrid proteins that has been used for this purpose is the hybrid protein encoded by lacZ -fragment C. This protein has been tested in vitro and in vivo to determine its activity in the hypoglossal system, and the detection of the labeled motor neurons was dependent on time post-injection [6062]. Since neuronal integrity is crucial for fragment C internalization, the transneuronal molecular pathway at neuromuscular junctions was intensively studied using this hybrid protein [63].…”
Section: Molecular Structure and Properties Of Fragment C: Toward mentioning
confidence: 99%
“…One of the most well-known hybrid proteins that has been used for this purpose is the hybrid protein encoded by lacZ -fragment C. This protein has been tested in vitro and in vivo to determine its activity in the hypoglossal system, and the detection of the labeled motor neurons was dependent on time post-injection [6062]. Since neuronal integrity is crucial for fragment C internalization, the transneuronal molecular pathway at neuromuscular junctions was intensively studied using this hybrid protein [63].…”
Section: Molecular Structure and Properties Of Fragment C: Toward mentioning
confidence: 99%
“…Furthermore, TTC-conjugation was shown to radically improve neuronal internalization of even large proteins, such as human IgG [32] or glucose oxidase [33], and to enable neuronal delivery of DNA coupled to the TTC with polylysine bridge [34]. Similar findings were found later using TTC coupled with beta-galactosidase (β-gal-TTC) delivered intramuscularly either as β-gal-TTC fusion protein [35,36,37] or as direct “naked DNA” plasmid injection in Xenopus [38] and in mice [37]. It was also demonstrated that β-gal-TTC is transneuronally transported to second and higher-order interconnected neurons [36] and that the transport to motor neurons was dependent on neuronal activity [39].…”
Section: Ttc As a Neuronal Retrograde Tracer And Carrier Of Therapmentioning
confidence: 85%
“…A similar problem exists with the experiments utilising TeNT heavy chain chemically conjugated to PLL to mediate gene delivery [107]. A separate study expressing fragment of TeNT within muscle cells avoided the use of polycations but concluded that the inclusion of the TeNT fragment encoded by a plasmid injected into muscle mass did not have any influence on the expression of the transfected gene [108].…”
Section: Attenuated Toxins As Nucleic Acid Delivery Systemsmentioning
confidence: 99%